Amiyah Languange and Islamic Education: Sosial and Cultural Interaction in the Dynamic of Islamic Education in Pasar Kliwon, Surakarta (1966-2020s) - Fahmi Kartika (Universitas Negeri Semarang, 2025)
This article examines the history and development of Colloquial Arabic (ʿĀmmiyya) usage and the role of Islamic education within the Diponegoro Islamic Education Foundation (YPID) in Pasar Kliwon, Surakarta. Known as the “Arab Quarter,” this area has long served as a site of interaction between the Arab-Hadrami community and Javanese society. Using historical and sociolinguistic approaches, the study shows how language and education function as two key media for building social integration and cultural identity from 1966 through the 2020s. The findings indicate that the everyday use of ʿAmmiyya among Surakarta’s Arab community has shifted in tandem with the community’s growing integration with local society. At the same time, Islamic educational institutions such as YPID have played a strategic role as multicultural bridges, sustaining cultural identity while fostering social harmony within a diverse Muslim context.